The contractor’s perception towards the new application of the new technology in managing constrcution / Mohamad Zuhairi Effendy - Effendy, Mohamad Zuhairi (2021)
The period of every construction sometimes look at their ‘technology that used’. The mixed method assessed whether the technology in previous study affected the contractor’s perception towards the application of the new technology in managing construction. The objective of this research to identify application of new technology that contractors used, to identify the perception of contractors when latest technology are used in construction. Thirty respondents were answered for data collection. This study found the type of new technology such drones, 3D printing, and etc. Structured google form for this case study.